2004
DOI: 10.1002/ijc.20325
|View full text |Cite
|
Sign up to set email alerts
|

High BRAF mutation frequency does not characterize all melanocytic tumor types

Abstract: Cutaneous melanoma (CM) is the most lethal form of skin cancer. Along with some benign melanocytic tumors, the majority shows BRAF or NRAS mutation, but it is not known whether these are essential to all forms of melanocytic neoplasia. We screened 79 melanocytic tumors of different types for BRAF and NRAS mutations and looked at MAPK pathway activity using immunohistochemistry in a subset. Significant differences in BRAF exon 15 mutation frequency were found: 14/16 (87.5%) in common acquired naevi (CANs), 9/12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
93
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 11 publications
7
93
1
2
Order By: Relevance
“…Similar to other investigators, we have previously shown that the highest incidence of BRAF mutations (82%) occurred in a group of congenital, common acquired, and atypical (dysplastic) nevi. 24,27,42,64 In contrast, 27% of primary invasive melanomas and 39% of metastatic melanomas had BRAF mutations in our series, which is similar to previously published data by other groups. 25,35,39 The high incidence of BRAF mutations in nevi suggests that this is an early event in melanocytic neoplasia.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to other investigators, we have previously shown that the highest incidence of BRAF mutations (82%) occurred in a group of congenital, common acquired, and atypical (dysplastic) nevi. 24,27,42,64 In contrast, 27% of primary invasive melanomas and 39% of metastatic melanomas had BRAF mutations in our series, which is similar to previously published data by other groups. 25,35,39 The high incidence of BRAF mutations in nevi suggests that this is an early event in melanocytic neoplasia.…”
Section: Discussionsupporting
confidence: 91%
“…25,[40][41][42][43][44][45][46] With the exception of the study by van Dijk et al, 40 which included an atypical Spitz nevus group, all other studies evaluated typical or classic Spitz nevi and/or spitzoid melanoma. The classic or typical Spitz nevus is usually readily distinguished from melanoma when standard histologic criteria are applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B-RAF mutations are also common in benign and dysplastic nevi (Pollock et al 2003;Yazdi et al 2003;Kumar et al 2004;Saldanha et al 2004), suggesting a role in the earliest stages of neoplasia. It is notable that nevi are considered growth-arrested and only rarely progress into melanoma, raising the possibility of BRAF V600E -induced checkpoint mechanisms operating to constrain malignant transformation.…”
Section: The Ras Family Of Proto-oncogenes: H-ras N-ras and K-rasmentioning
confidence: 99%
“…In contrast, melanocytic tumours such as uveal melanomas rarely show BRAF and NRAS mutations (Kilic et al, 2004;Saldanha et al, 2004;Janssen et al, 2008;Maat et al, 2008). Recently, somatic mutations in the heterotrimeric G protein alpha subunit q (GNAQ) have been found to be associated with dominant dark skin in a large-scale mutagenesis screen of inbred C3HeB/FeJ mice (Van Raamsdonk et al, 2004).…”
mentioning
confidence: 99%